Surface molecules of Leishmania: from virulence determinants to therapeutic and vaccine targets - Reis, Túlio Custódio [UNESP]; Yagi, Ana Clara Lunardi [UNESP]; Ramos, Ana Laura Dias [UNESP]; Velásquez, Angela Maria Arenas [UNESP]; Coelho, Natália Caroline Costa [UNESP]; Graminha, Márcia A. S. [UNESP] (Elsevier, 2025)
Leishmaniasis is a group of neglected tropical diseases (NTDs) caused by protozoa of the genus Leishmania that affect vulnerable populations in tropical and subtropical regions. The disease manifests in cutaneous, mucocutaneous, and visceral clinical forms. This major public health disease presents high morbidity, and despite the global impact of leishmaniasis, there are few therapeutic options available and no currently licensed human vaccines. Besides, the available therapeutic agents are associated with high toxicity and treatment failure. These limitations highlight the importance of identifying new therapeutic targets, which will contribute to the development of more effective, safer and shorter treatment options. In this context, surface molecules of Leishmania emerge as attractive therapeutic targets due to their roles in host cell adhesion, immune evasion, and intracellular survival. In addition to their translational potential for drug discovery and vaccine development, these surface molecules are key virulence factors that play central roles in parasite biology and disease pathogenesis. Understanding their structure and function is essential not only for elucidating mechanisms of host–parasite interaction, but also for identifying novel therapeutic and prophylactic strategies. Importantly, molecules such as GP63 (a major surface metalloprotease), LPG (lipophosphoglycan), and KMP-11 (kinetoplastid membrane protein 11) combine essential biological functions with demonstrated immunogenic properties, making them promise as targets for both chemotherapeutic and prophylactic interventions. This review aims to explore the structural and functional characteristics of major surface virulence factors in Leishmania, highlighting their roles in the parasite–host interaction and discussing their translational potential for therapeutic and vaccine development.
Surface molecules of Leishmania: from virulence determinants to therapeutic and vaccine targets
Keywords: Leishmania; Surface molecules; Macrophage; GP63